Enhancement of ovarian maturation in bronze featherback Notopterus notopterus through pregnant mare serum gonadotropin for sustainable aquaculture and conservation - MUSLIM MUSLIM; ELIKA PITRIANI; SELLY OKTARINA; NADILA NUR KHOTIMAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Muslim, Pitriani E, Oktarina S, Khotimah NN. 2026. Enhancement of ovarian maturation in bronze featherback Notopterus notopterus through pregnant mare serum gonadotropin for sustainable aquaculture and conservation. Biodiversitas 27 (1): d270121. https://doi.org/10.13057/biodiv/d270121. The bronze featherback Notopterus notopterus is a freshwater fish of high economic value whose population is declining due to overfishing and habitat destruction. This study evaluated the effectiveness of pregnant mare serum gonadotropin in inducing ovarian maturation in N. notopterus, addressing reproductive challenges that hinder its domestication and conservation. A total of 45 female fish (mean weight 50-55 g and total length 18-20 cm) at the second stage of ovarian maturity were injected intramuscularly with pregnant mare serum gonadotropin doses of 0, 1.0, 1.25, and 1.5 mL kg⁻¹ body weight. Observations were conducted for nine days with parameters including Ovi-Somatic Index (IOS), Hepato-Somatic Index (IHS), oocyte diameter, fecundity, cholesterol levels, and ovarian maturity level. The results indicated that pregnant mare serum gonadotropin significantly influenced IOS, oocyte diameter, fecundity, and ovarian maturity level (ANOVA, P<0.05; post-hoc LSD test), whereas it showed no significant effect on IHS and cholesterol levels (p>0.05). A dose of 1.5 mL kg⁻¹ produced the highest IOS, oocyte diameter, and fecundity values (378 eggs), as well as ovarian maturity levels up to stage V (mature). This study provides that hormonal induction using pregnant mare serum gonadotropin effectively stimulates ovarian development in N. notopterus, offering a biological solution to reproductive challenges that limit domestication success. By enhancing spawning success rates, reducing dependence on wild-caught broodstock, and enabling the establishment of captive breeding protocols, this hormonal induction technique offers practical tools for ex-situ conservation and directly contributes to biodiversity protection by supporting the long-term sustainability of N. notopterus populations. These findings show that aquaculture-based reproductive management supports SDG 14 by promoting sustainable use of aquatic resources. Hormonal induction serves as a bridge between reproductive biotechnology and conservation, helping restore freshwater biodiversity through domestication-based recovery strategies.